Erythema multiforme with reference to atypical presentation in an HIV-positive patient following antiretroviral therapy discontinuation - Lugović Mihić, Liborija (Array, 2009)
Summary: Erythema multiforme (EM) is a skin disease caused by numerous potential triggering agents. It is characterized by symmetrically distributed, round, erythematous iris lesions, with remarkable tendency of recurrence. The purpose of this randomized retrospective study was to summarize our experience concerning the etiology, clinical variants and management of EM. We present 12 EM patients, along with laboratory, clinical and histopathologic analysis, and an overview of the treatment used. According to clinical presentation and histopathologic analysis, there were six cases of EM major, five cases of EM minor and one case of Stevens-Johnson syndrome. In five patients, EM was associated with the use of certain drugs (terbinafine, azithromycin, diclofenac, piroxicam). In three patients, the disease was triggered by the herpes simplex virus infection. In four cases, the etiologic factor (involved in the occurrence) of EM remained unknown. We also present an unusual case of an HIV-positive patient with multiple acral target lesions without mucosal involvement, which developed upon antiretroviral therapy discontinuation. To our knowledge, no case of such EM occurrence has yet been reported. There are various etiologic factors and numerous clinical presentations of EM, including acral target lesions and atypical widely distributed cutaneous and mucosal lesions